Crecimiento del guapote tigre, Cichlasoma managuense (Pisces: Cichlidae) bajo régimen de cultivo intensivo en estanques de tierra - Günther, Jorge (1996)
The jaguar cichlid (Cichlasoma managuense) was cultured for 300 days in twa earthen ponds (2.4 fishlm') with artificial diets. There was a marked grawth difference between males (mean weight 246.7 g after 300 days) and females (122.5 g). The highest weight attained in this period was abaut 400 g. The jaguar guapote was nat able to control its own reproduction, since at the end of the experiment hundreds of fry were coJIected. Further triaIs shouId be canducted with maIe monosex papulations onIy.